Text, speech and dialogue 14th international conference, TSD 2011, Pilsen, Czech Republic, September 1-5, 2011 : proceedings - Habernal, Ivan; Matousek, Václav 1948 (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Text, Speech and Dialogue, TSD 2011, held in Pilsen, Czech Republic, in September 2011. The 53 papers presented together with 2 invited talks were carefully reviewed and selected from 110 submissions. The main topic of this year's conference was "integrating modern Web with speech and language technologies". This year the Third International Workshop on Balto-Slavonic Natural Language was affiliated to TSD. The present book contains 8 contributions from this workshop.